A Comparison Study of Brine Desalination using Direct Contact and Air Gap Membrane Distillation (Journal of Engineering, 2019)
Membrane distillation (MD) is a hopeful desalination technique for brine (salty) water. In this research, Direct Contact Membrane Distillation (DCMD) and  Air Gap Membrane Distillation (AGMD) will be used. The sample used is from Shat Al –Arab water (TDS=2430 mg/l). A polyvinylidene fluoride (PVDF) flat sheet membrane was used as a flat sheet form with a plate and frame cell. Several parameters were studied, such as; operation time, feed temperature, permeate temperature, feed flow rate. The results showed that with time, the flux decreases because of the accumulated fouling and scaling on the membrane surface. Feed temperature and feed flow rate had a positive effect on the permeate flux, while permeate temperature had a reverse effect on permeate flux. It is noticeable that the flux in DCMD is greater than AGMD, at the same conditions. The flux in DCMD is 10.95LMH, and that in AGMD is 7.14 LMH.  In AGMD, the air gap layer made a high resistance. Here the temperature transport reduces in the permeate side of AGMD due to the air gap resistance. The heat needed for AGMD is lower than DCMD, this leads to low permeate flux because the temperature difference between the two sides is very small, so the driving force (vapor pressure) is low.